Acetylene coupler builds strong and tunable diradical organic molecular magnets. (5th May 2021) - Ma, Jiapeng; Yuan, Yuan; Kang, Baotao; Lee, Jin Yong
Abstract : An acetylene coupler builds strong and flexible organic molecular magnets. Abstract : Sufficiently strong molecular magnets are used in small modern electronic and spintronic devices. Diradical organic magnetic molecules (OMMs) are promising options due to their lightness, flexibility, and the low energy required for their synthesis. In this field, the coupler is a dominating component, though acetylene, the shortest coupler, has not been studied for this use. In this study, we conceptualize several model systems using an acetylene link to couple different monoradicals. We simulated their magnetic strength using the broken symmetry method via density functional theory calculations. Our results show that the acetylene (–CC–) coupler gives much larger J values than the ethylene (–CC–) coupler. Acetylene coupling a phenoxyl (PO) and a nitronyl nitroxide (NN) diradical is the strongest ferromagnetic diradical OMM, and acetylene coupling a PO bisradical is the strongest anti-ferromagnetic diradical OMM. Moreover, we found that the magnetic strength is dependent on the coupler length and torsion, but is independent of the bending. Since only a very small energy barrier is needed, it is feasible to use torsion to tune a diradical OMM's magnetic strength. Our results are also beneficial for the rational design and synthesis of diradical OMMs.